Modernisation and extension of InetVis: a network security data visualisation tool - Johnson, Yestin (Rhodes University, Faculty of Science, Department of Computer Science, 2019)
This research undertook an investigation in digital archaeology, modernisation, and revitalisation of the InetVis software application, developed at Rhodes University in 2007. InetVis allows users to visualise network traffic in an interactive 3D scatter plot. This software is based on the idea of the Spinning Cube of Potential Doom, introduced by Stephen Lau. The original InetVis research project aimed to extend this concept and implementation, specifically for use in analysing network telescope traffic. The InetVis source code was examined and ported to run on modern operating systems. The porting process involved updating the UI framework, Qt, from version 3 to 5, as well as adding support for 64-bit compilation. This research extended its usefulness with the implementation of new, high-value, features and improvements. The most notable new features include the addition of a general settings framework, improved screenshot generation, automated visualisation modes, new keyboard shortcuts, and support for building and running InetVis on macOS. Additional features and improvements were identified for future work. These consist of support for a plug-in architecture and an extended heads-up display. A user survey was then conducted, determining that respondents found InetVis to be easy to use and useful. The user survey also allowed the identification of new and proposed features that the respondents found to be most useful. At this point, no other tool offers the simplicity and user-friendliness of InetVis when it comes to the analysis of network packet captures, especially those from network telescopes.
Keywords: Data visualization; InetVis (Application software)